Electrospinning of thermoplastic polyurethane microfibers and nanofibers from polymer solution and melt. Issue 3 (10th May 2012) - Dasdemir, Mehmet; Topalbekiroglu, Mehmet; Demir, Ali
Abstract: Electrospinning technique was used to produce ultrafine fibers from thermoplastic polyurethane (TPU). A direct comparison between melt and solution electrospinning of TPU was provided for the evaluation of process–structure relationship. It was found that the deposition rate of melt electrospinning (0.6 g h −1 ) is four times higher than that of solution electrospinning (0.125 g h −1 ) for TPU under the same processing condition. However, the average fiber diameters of solution electrospun TPUs (220–280 nm) were much lower than those of melt electrospun TPUs (4–8 μm). The effect of processing variables including collection distance and electric field strength on the electrospun fiber diameter and morphology was also studied. The findings indicate that increasing the electric field strength yielded more electrical forces acting on polymer jet and resulted in a decrease in fiber diameter as a result of more fiber drawing in both solution and melt electrospun fibers. It was also demonstrated that increasing the collection distance led to an improvement in the solidification of melt electrospun fibers and thus less fused fibers were obtained. Finally, a close investigation of fiber structures revealed that melt electrospun TPU fibers had smooth surface, whereas solution electrospun TPU fibers showed high intensity of cracks on the fiber surface. © 2012 Wiley Periodicals, Inc. J. Appl. Polym. Sci., 2013 Abstract :